Museums, Transculturality, and the Nation-State : Case Studies from a Global Context - Leeb, Susanne; Leeb, Susanne; Samuel, Nina; Samuel, Nina; Dávila, Sebastián Eduardo; Ginwala, Natasha; Hanna, Monica; Kahlon, Rajkamal; Milevska, Suzana; Shatanawi, Mirjam; Singh, Kavita; Spero Adotevi, Stanislas; et al. (Edition Museum, 2022)
While the nation-state gave rise to the advent of museums, its influence in times of transculturality and post-/decolonial studies appears to have vanished. But is this really the case? With case studies from various geo- and sociopolitical contexts from around the globe, the contributors investigate which role the nation-state continues to play in museums, collections, and heritage. They answer the question to which degree the nation-state still determines practices of collection and circulation and its amount of power to shape contemporary narratives. The volume thus examines the contradictions at play when the necessary claim for transculturality meets the institutions of the nation-state.